SENSORY ANALYSIS: THE ATTRIBUTES OF PACKAGING AND PHARMACEUTICAL FORMS OF NAIL STRENGTHENERS COMMERCIALIZED IN BRAZIL - Silva, Jhordana De Oliveira; Ferreira, Lilian De Abreu (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: Conduct effective sensory method on three nail strengtheners with different packaging and pharmaceutical forms commercialised in Brazil. Methods: Two affective tests, of acceptance and sorting-preference, and a purchase intention test were conducted. The attributes packing appearance, ease of application provided by the packaging and texture and spreadability of the pharmaceutical form were evaluated, using the hedonic scale of 9 points to evaluate the attributes and 5 points to assess the intention of buying. The sensory panel was composed of 32 judges, consumers or potential consumers. Results: On the acceptance test, the pen with emulsion pharmaceutical form obtained was most preferred on the appearance of the package (7.88) and ease of application (7.72) attributes. The sample most preferred on texture and spreadability attribute was the nail polish bottle with brush containing enamel base pharmaceutical form (8.06), followed by pen bottle containing emulsion (6.75) and dropper bottle containing oil as pharmaceutical form (5.41) respectively, with statistical significance (p<0.05). All samples were higher with significant difference (p<0.05) compared with the dropper bottle containing oil on purchase intent. Conclusion: It was demonstrated that pen bottle had the highest preference on package appearance and ease of application attributes and the enamel base pharmaceutical form had the highest preference in the texture and spreadability attribute. The nail polish bottle containing the pharmaceutical form enamel base showed the highest preference in purchase intention and sorting-preference test.